EXTENDED SPECTRUM BETA-LACTAMASE (ESBL) PRODUCING ENTEROBACTERALES: CLASSIFICATION AND RESISTANCE GENETIC BACKGROUND - Milić, Marija; Mijač, Vera (Medicinski podmladak, 2019)
Beta-lactam antibiotics are one of the most important ones in clinical practice and most commonly prescribed drugs. There are few possible mechanisms of beta-lactam resistance. Beta-lactamase opens the β-lactam ring, deactivating the molecule’s antibacterial properties, and among them, Extended-spectrum beta-lactamases (ESBL) are the most important. Antibiotic resistance gene can both be located on chromosome, or on plasmids. Betalactamases share the ability to hydrolyse penicillin, cephalosporin and monobactam, but not carbapenems and cephamycin, and yet, they are inhibited by clavulanic acid and/or tazobactam. Far most important in clinical practice are CTX-M enzymes, followed by TEM and SHV. Other less widespread ones are VEB, PER, GES, TLE, IBC, BES, BEL and others. Over the last years the presence of antibiotic resistant bacteria has been shown outside the clinical environment, including water, soil and food producing animals. If this problem persists in all over the world, carbapenems might be the first line antibiotics. Considering the present situation, antimicrobial resistance could be one of the greatest challenges in modern medicine, and it is important to ensure that antibiotics are prescribed only when needed.